Implicit Pension Debt, Transition Cost, Options, and Impact of China's Pension Reform : A Computable General Equilibrium A - Wang, Zhi (The World Bank, 2001)
China's population is aging rapidly: the old-age dependency ratio will rise from 11 percent in 1999 to 25 percent in 2030 and 36 percent in 2050. Currently, three workers support one retiree; without reform, the system dependency ratio will climb to 69 percent in 2030 and 79 percent in 2050. The pension system has been in deficit, with an implicit pension debt in 2000 as high as 71 percent of GDP. The lack of an effective, sustainable pension system is a serious obstacle to Chinese economic reform. The main problems with China's pension system—the heavy pension burdens of state enterprises and the aging of the population—have deepened in recent years. Using a new computable general equilibrium model that differentiates between three types of enterprise ownership and 22 groups in the labor force, Wang, Xu, Wang, and Zhai estimate the effects of pension reform in China, comparing various options for financing the transition cost. They examine the impact that various reform options would have on the system's sustainability, on overall economic growth, and on income distribution. The results are promising. The current pay-as-you-go system, with a notional individual account, remains unchanged in the first scenario examined. Simulations show this system to be unsustainable. Expanding coverage under this system would improve financial viability in the short run but weaken it in the long run. Other scenarios assume that the transition cost will be financed by various taxes and that a new, fully funded individual account will be established in 2001. The authors compare the impact of a corporate tax, a value-added tax, a personal income tax, and a consumption tax. They estimate the annual transition cost to be about 0.6 percent of GDP between 2000 and 2010, declining to 0.3 percent by 2050.